DATA-DRIVEN PERFORMANCE EVALUATION AS THE FOURTH PILLAR OF EDUCATIONAL HUMAN RESOURCE MANAGEMENT AT SD NEGERI KARANGREJO 01, SEMARANG - Juan Lestari Paiki; Tri Prasetyo Handayani; Fitria; Muji Astuti; Novia Indriani; Ngurah Ayu Nyoman Murniati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Educational human resource management requires an integrated data-driven evaluation system to continuously enhance teacher capacity. This study aims to analyze the implementation of Data-Driven Performance Evaluation as the Fourth Pillar of Educational Human Resource Management at SD Negeri 01 Karangrejo, Semarang, focusing on its sensory, integrative, and motor functions, alongside its enabling and hindering factors. Employing a qualitative case study design, data were collected through non-participant observation, documentation, and semi-structured interviews with four informants (the principal and three teachers), and analyzed using thematic analysis. The findings reveal that while the sensory function is robustly institutionalized through digital platforms (e-Kinerja and Rumah Pendidikan) and the integrative function is enriched by organic, informal teacher reflections, the system suffers from